2022
DOI: 10.1016/j.ajog.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection during pregnancy and risk of preeclampsia: a systematic review and meta-analysis

Abstract: OBJECTIVE To examine the relationship between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy and the risk of preeclampsia. DATA SOURCES MEDLINE, EMBASE, POPLINE, CINAHL, LILACS, and WHO COVID-19, Chinese, and preprint databases (all from December 1, 2019 to May 31, 2021). Google Scholar, bibliographies, and conference proceedings were also searched. STUDY ELIGIBILITY CRITERIA Observational studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
3
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(183 citation statements)
references
References 168 publications
9
132
3
9
Order By: Relevance
“…Another finding that worsens the prognosis is the association between COVID-19 and pre-eclampsia. This association has been observed in a longitudinal study 3 and in a systematic review 4 . Pregnant women infected with SARS-CoV-2 have a significant 62% greater likelihood of developing pre-eclampsia than those without infection, including a higher risk of presenting the worst conditions of pre-eclampsia in its severe form, HELLP syndrome and eclampsia, according to the findings of a systematic review 4 .…”
Section: Pregnant Women With Sars-cov-2supporting
confidence: 54%
See 1 more Smart Citation
“…Another finding that worsens the prognosis is the association between COVID-19 and pre-eclampsia. This association has been observed in a longitudinal study 3 and in a systematic review 4 . Pregnant women infected with SARS-CoV-2 have a significant 62% greater likelihood of developing pre-eclampsia than those without infection, including a higher risk of presenting the worst conditions of pre-eclampsia in its severe form, HELLP syndrome and eclampsia, according to the findings of a systematic review 4 .…”
Section: Pregnant Women With Sars-cov-2supporting
confidence: 54%
“…With the progression of the disease and adequate studies in pregnant women, it has been shown that this group of the population is associated with a higher risk and severity of the disease 1 . About 10% of pregnant women evolve severely, there is a higher risk of admission to the intensive care unit (ICU), the need for mechanical ventilation, maternal deaths, a higher risk of pre-eclampsia, premature births, and neonatal complications [2][3][4] . Vaccines based on an mRNA platform have become one of the safest and most widely used alternatives for combatting SARS-CoV-2 5 infections.…”
Section: Introductionmentioning
confidence: 99%
“…One type of infection that is currently very prominent is exposure to the SARS-CoV-2 coronavirus, the cause for COVID-19. It has been linked to a greater risk for severe PE [ 135 , 136 , 137 , 138 ]. It was recently reviewed that almost 38% of pregnancies infected by COVID-19 have markers of uteroplacental malperfusion, including fibrin deposition, infarction, decidual vasculopathy, accelerated villous hyperplasia, distal villous hypoplasia, and retroplacental hemorrhage, as well as placental inflammation [ 139 , 140 ].…”
Section: Pro-inflammatory States As Risk Factors For Placental Ischemic Disease and Pementioning
confidence: 99%
“…The greater the severity of SARS-CoV-2, the higher the risk of preterm birth, which is thought to be related to an increase in medically indicated, rather than spontaneous, preterm birth (57). A systematic review and meta-analysis also indicated an association between SARS-CoV-2 infection during pregnancy and the odds of preeclampsia (pooled odds ratio 1.58, 95% CI 1.39-1.80; P<0.001; I 2 =0%; 11 studies) (58). This association was also found for preeclampsia with severe features, eclampsia, and HELLP syndrome.…”
Section: Sars-cov-2 Infection During Pregnancy and Preterm Birthmentioning
confidence: 99%